Etiology, Clinical Profile and Outcome of Acute Respiratory Failure in Adults in Kashmir Valley (North India): A Hospital Based Prospective Study - Wani, Dr. Abdul Ahad; Ahmad, Dr. Manzoor; Shafi, Dr. Amir; Naik, Dr. Muzaffar; Bhat, Dr. Tariq; Naqash, Dr. Mubarik (International Journal of Innovative Research in Medical Science, 2020)
Background: A prospective study to evaluate the etiological factors, clinical features, treatment modalities and outcome of acute respiratory failure in adults (> 18 years age) in Kashmir valley north India is important to understand the epidemiological trends and the detailed disease manifestations. Methods: We conducted a hospital based prospective study which was conducted over a period of one and half year, initiated in January 2018 and concluded in 2019 in tertiary care hospital. 100 patients above the age of 18 years with acute respiratory failure were actively enrolled. Acute respiratory failure was identified by the defined criteria, in any patient presenting with respiratory arrest / respiratory failure/respiratory distress with SPO2 ≤92%, breathlessness of <2 weeks duration and altered respiratory pattern. The patients who fulfilled at least one of the following criteria of respiratory failure were included in the study. (I)Arterial PaO2<70mmHg, (II)Peripheral O2 saturation ≤92% breathing in room air (III) Arterial PaCO2 ≥45mmHg (IV) PH ≤7.35 with signs and symptoms of respiratory distress. Results: Of the total of 100 patients included in the study, the mean age of the cohort was 55 SD ± 19 years. The cause of respiratory failure were COPD with acute exacerbation (45%), sepsis with MODS (20%), acute O.P. poisoning (12%), massive ICH (4%), acute liver failure with respiratory failure(3%), ARDS(3%),acute opioid poisoning with respiratory failure (3%), acute LVF (2%),PTE (2%), anaphylaxis (2%), acute M.I. (1%), myasthenia crisis (2%) strangulation with asphyxia (1%) and fat embolism (1%). Type-2 respiratory failure was found in 45% while type-1 respiratory failure was found in 55% patients. 55 % patients needed invasive ventilation; 26% patients needed NIV. While 19% patients needed high flow oxygen with nasal cannula. Conclusion: Commonest cause of acute respiratory failure in adults is COPD with acute exacerbation (45%) followed by sepsis with MODS (20%). Type 2 respiratory failure accounted for 45% while type 1 accounted for 55% of acute respiratory failure in adults. In our study, COPD is the leading cause of death in acute respiratory failure followed by sepsis with MODS.